Factors Associated with the Uptake of Long-Acting Reversible Contraception and Contraceptive Use in Postpartum People with HIV at a Single Tertiary Care Center - Youniss, Lara; Bui, Lilian; Cejtin, Helen; Schmidt, Julie; Premkumar, Ashish (American Journal of Perinatology, 2024)
Objective This study aimed to elucidate factors contributing to uptake of highly effective contraception, including permanent contraception, and no contraceptive plan among postpartum people with HIV (PWHIV).Study Design A retrospective cohort analysis was conducted to correlate postpartum birth control (PPBC) with sociodemographic and biomedical variables among postpartum PWHIV who received care at The Ruth M. Rothstein CORE Center and delivered at John H. Stroger, Jr. Hospital of Cook County in Chicago, from 2012 to 2020.Results Earlier gestational age (GA) at initiation of prenatal care, having insurance, and increased parity are associated with uptake of highly effective contraception. Meanwhile, later GA at presentation increased odds of having no PPBC plan.Conclusion Early prenatal care, adequate insurance coverage, and thorough PPBC counseling are important for pregnant PWHIV.Key Points
Keywords: HIV; postpartum contraception; long-acting reversible contraception; insurance payor